Boron mining and enrichment waste: A promising raw material for porcelain tile production - Karadagli, Emirhan; Cicek, Bugra (WILEY, 2020)
Boron mining and enrichment waste (BW) from boric acid (H3BO3) production is a by-product of the boron industry. BW exhibits B2O3 contents of 16-31 wt%, and therefore, could be used to effectively lower the sintering temperature of ceramics without increasing their thermal expansion coefficient. Herein, we introduced 3-10 wt% of BW to a formulation used for commercial porcelain tile production, and achieved a sintering temperature decrease of 38 degrees C (to 1195 degrees C). The resulting porcelain tiles exhibited a strength of 44.80 MPa and water absorption percentage of 0.01%, and therefore, met TS ISO EN 10545 requirements. Thus, this study paves the way for the use and valorization of BW in the production of porcelain tiles and could inspire the search for other opportunities to utilize BW in ceramic production.
Keywords: borates; ceramic tile; low temperature; waste disposal; FLY-ASH; GLASS-CERAMICS; BOTTOM ASH; Materials Science